An exploratory study of the motivations, expectations and impact for scientists coordinating science engagement activities - Bento, Afonso; Catarino, Ana Isabel; Moscoso, Joana A. (Frontiers in Communication, 2023)
Public engagement with science and science outreach initiatives have intensified their efforts to prioritize inclusivity and diversity as main core features. In this work, we describe a European-wide science engagement program designed to promote scientific literacy and multilingualism. The program consists of small-group, in-person interventions that foster interactions between scientists and school students from the same migrant community through workshops, delivered in a shared heritage language. Through an exploratory qualitative analysis of open-ended surveys, we analyzed the motivations, expectations and outcomes of scientists enrolled as coordinators in the program. We observed that the scientists coordinating the program have two major sets of motivations to participate: societal motives and personal motives. Furthermore, our results indicate a strong alignment between scientists' expectations and outcomes, in particular regarding the attainment of transferable skills, networking and personal fulfilment. We also explored in more depth the category of personal fulfilment as a motivation, expectation and outcome, leading us to identify the in-person feature of the workshops, as well as the shared characteristics of scientists and audience, as potential engagement factors to be explored in future research. We argue that the concept of embodied narratives, where scientists serve as visible living proof of achievement to a particular audience, can help frame this research.